Kebijakan Perdagangan Gula Internasional dan Pengaruhnya terhadap Tata Niaga Gula di Indonesia - Hijrah Nasir; Nurshinta Anggia; Desri Gunawan (Journal of World Trade Studies, 2015)
The world sugar industries had experienced fluctuation over the past decades. In the recent time, sugar consumption increased rapidly while the production reduced gradually. This condition is also augmented by international agreement in WTO through modalities draft, which was created on July 2008. This draft required the parties to follow the tariff reduction formula and eliminate non- tariff measures that are inconsistent with WTO agreements. Nevertheless, the developing countries have been proposed the proposal to protect the sensitive sectors comprises sugar, rice, corn, and soybeans for exclusion from WTO trade liberalization. This article intends to analyse sugar trade policy in Indonesia. Sugar is one of strategic industrial commodity products in Indonesia that had enjoyed the progressive enhancement during the 1930s. However, it became deteriorated recently due to the declining of production while the demands rose dramatically. This article argues that soaring consumption, poor infrastructures and high production cost have triggered a significant increase in sugar import. This in turn only benefits the sugar importers.